Analysis of implementing information sharing based on maritime-related innovation platforms: a multi-stakeholder perspective - Gu, Xiaohan (My University, 2022)
The maritime industry has been influenced by rapid technological developments for decades which are also increasing the requirements of the industry and the maritime industry needs to rely on technological development and innovation as well. Information communication and te chnologies (ICT) provide various benefits to maritime management, open innovation platform as an effective form of ICT originates from innovation intermediary, playing an increasingly important role in connecting the supply and demand, promoting innovation cooperation and facilitating technological progress. The dissemination of such open platforms and many other similar information systems is still in infancy. Therefore, research is necessary because it enriches the understanding of the maritime sector that influence the communication and information sharing in the cross organizational information systems in this industry. The overall aim of the thesis is to understand the stakeholders’ attitudes to the maritime open innovation platforms especially on the needs and expectations of platforms. Also, to detect the barriers of maritime-related platforms and further give policy implications on the developers of platforms. Based on current research on innovation eco systems analyze a case OIP from a stakeholders’ perspective thereby identifying strengths and weaknesses to recommend general changes to the case OIP, both functional and strategic.
Keywords: Open innovation platform, cluster, stakeholder, innovation ecosystem